The Effect of Temperature and Brewing Time for Herbal Tea with Bay Leaves and Soursop Leaves on Sensory Quality and Antioxidant Activity as a Functional Drink for Hypertension Sufferers - Novitasari, Tiara; Puspita, Theresia; Razak, Maryam (Politeknik Kesehatan Kemenkes Malang, 2024)
Abstract Background: Hypertension basically tends to be difficult to control both with medication and medical procedures because this disease has an unstable nature. Antioxidant compounds are generally used in food as health protection agents because they can prevent oxidation in the body so they can play a role in preventing various diseases. Antioxidants can relax and dilate blood vessels and lower blood pressure. Objective: To analyze the effect of temperature and brewing time for herbal tea made from bay leaves and soursop leaves on sensory quality and antioxidant activity as a functional drink for hypertension sufferers. Design: Type of experimental research with 8 treatment levels and 2 repetitions in organoleptic analysis and antioxidant activity. Results: The results showed that temperature and brewing time had a significant influence (p>0.05) on color, aroma, taste, and clarity. The results of the analysis that have been carried out on the antioxidant activity obtained in bay leaf and soursop leaf herbal tea with 8 levels of treatment, namely: P1 = 97.7 ppm antioxidant activity, P2 = 88.4 ppm antioxidant activity, P3 = 69.8 ppm antioxidant activity antioxidant, P4 = 83 ppm antioxidant activity, P5 = 98.5 ppm antioxidant activity, P6 = 100.4 ppm antioxidant activity, P7 = 108.7 ppm antioxidant activity, P8 = 111.6 ppm antioxidant activity. The P3 treatment level is the best treatment level and the result value (Nh) is 0.84. Conclusion: Temperature treatment and brewing time for bay leaf and soursop leaf herbal tea had no significant influence on the sensory quality of the hedonic test (color, aroma, taste, and clarity). Key words: Hypertension; Bay leaf; soursop leaf; antioxidant activity.